2023
DOI: 10.1039/d3sc00697b
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired nucleobase-containing polyelectrolytes as robust and tunable adhesives by balancing the adhesive and cohesive properties

Abstract: Supramolecular polymeric adhesives inspired by nature have been strongly pursued by scientists, since they possess strong but dynamic reversible adhesive behaviors concurrently. Optimizing the adhesive and cohesive properties is of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…(e) The A 5% EP-B 3 O 3 DEAs can still carry a weight of 2.5 kg after soaking in water for 30 days. (f) Comparison of the adhesion at room temperature, high temperature, ultralow temperature, hydrolysis stability, and tensile strength of the detachable adhesives reported in this study and other research groups. , …”
Section: Resultsmentioning
confidence: 85%
“…(e) The A 5% EP-B 3 O 3 DEAs can still carry a weight of 2.5 kg after soaking in water for 30 days. (f) Comparison of the adhesion at room temperature, high temperature, ultralow temperature, hydrolysis stability, and tensile strength of the detachable adhesives reported in this study and other research groups. , …”
Section: Resultsmentioning
confidence: 85%
“…Previous studies have also showed that T g and T m decrease with an increase in the length of alkyl chain; thus, P2 exhibited lower T g and T m than P1. [15,16] However, P3 was not inconsistent with the above-mentioned rule, because it was a crystalline solid inherited from its reactant (compound 10), and the DSC results of compound 10 support this explanation (Figure S27). [16] Hence, the alkyl chain moiety can tune the thermomechanical properties of these molecular solids.…”
Section: Resultsmentioning
confidence: 65%
“…Annealing conditions significantly influence the adhesive strength of bonded samples. 48,49 Given the sensitivity of linear PPA to sonication and elevated temperatures, 50 we chose to employ a solvent-assisted bonding method to retain the polymer composition, while also providing the polymer chains with freedom of motion to form favorable intermolecular interactions with a substrate. We sought to develop a straightforward procedure for bonding substrates with linear PPA that (i) preserved the flexibility and properties of the polymer, (ii) maximized adhesive strength, and (iii) provided evidence regarding the structure–property relationships that contribute to adhesion.…”
Section: Resultsmentioning
confidence: 99%